2012
DOI: 10.1016/j.ydbio.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Germ cells are not the primary factor for sexual fate determination in goldfish

Abstract: The presence of germ cells in the early gonad is important for sexual fate determination and gonadal development in vertebrates. Recent studies in zebrafish and medaka have shown that a lack of germ cells in the early gonad induces sex reversal in favor of a male phenotype. However, it is uncertain whether the gonadal somatic cells or the germ cells are predominant in determining gonadal fate in other vertebrate. Here, we investigated the role of germ cells in gonadal differentiation in goldfish, a gonochorist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 34 publications
6
83
0
Order By: Relevance
“…In contrast, Cyp19a1a, an ovarian-specific gene, was not detected in nanos3 mutant XX gonads. On the other hand, germ-cell deficiency in XY tilapia testis did not affect the sex differentiation in somatic cells, which is consistent with the results from the four fishes mentioned above (Slanchev et al 2005;Kurokawa et al 2007;Fujimoto et al 2010;Goto et al 2012). Together, these results demonstrate that the effects of germ-cell ablation gonadal fate are species-specific.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, Cyp19a1a, an ovarian-specific gene, was not detected in nanos3 mutant XX gonads. On the other hand, germ-cell deficiency in XY tilapia testis did not affect the sex differentiation in somatic cells, which is consistent with the results from the four fishes mentioned above (Slanchev et al 2005;Kurokawa et al 2007;Fujimoto et al 2010;Goto et al 2012). Together, these results demonstrate that the effects of germ-cell ablation gonadal fate are species-specific.…”
Section: Discussionsupporting
confidence: 90%
“…Germ cells were lost in the gonads after nanos2 and nanos3 mutation, as demonstrated by GFP labeling and Vasa staining. In line with the results obtained from medaka and zebrafish (Slanchev et al 2005;Kurokawa et al 2007), but contrary to those from goldfish and loach (Fujimoto et al 2010;Goto et al 2012), our study showed that germ-cell-deficient XX tilapia displayed femaleto-male sex reversal after nanos3 mutation. In contrast, Cyp19a1a, an ovarian-specific gene, was not detected in nanos3 mutant XX gonads.…”
Section: Discussionsupporting
confidence: 89%
“…Dnd plays an important role in germ plasm RNAs stabilization through binding their 3′UTR and inhibiting miRNAs targeting (Kedde et al, 2007). Depletion of Dnd abolishes PGC in teleost including zebrafish (Weidinger et al, 2003), loach (Fujimoto et al, 2010), goldfish (Goto et al, 2012), Atlantic salmon (Wargelius et al, 2016), (Hong et al, 2016), and gibel carp (Liu et al, 2015a). Recent study in medaka has revealed that it is dnd but not dazl or vasa, functions as a key specifier of PGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Dnd has been cloned and identified in many vertebrates, including mouse (Youngren et al, 2005), zebrafish (Weidinger et al, 2003), chicken (Aramaki et al, 2009), Xenopus (Horvay et al, 2006), medaka (Liu et al, 2009;Hong et al, 2016), loach (Fujimoto et al, 2010), goldfish (Goto et al, 2012), sterlet sturgeon (Linhartova et al, 2015), and Atlantic salmon (Wargelius et al, 2016). In most of examined teleost fishes, such as zebrafish, medaka, loach, goldfish, sterlet sturgeon, and Atlantic salmon, dnd is specifically expressed in PGCs, and the dnd translation block or depletion completely abolishes PGCs during early embryogenesis (Weidinger et al, 2003;Fujimoto et al, 2010;Goto et al, 2012;Hong et al, 2016;Wargelius et al, 2016). In some species, however, the dnd expression in adults appears to be different with sex.…”
Section: Introductionmentioning
confidence: 99%
“…Females can also be mated to WT males to produce clutches of embryos without maternal gene products. Germ-line replacement has now been used on a wide variety of fish species and even in cross-species transplants, opening up additional opportunities for research on gamete development (Saito et al 2008;Shimada and Takeda 2008;Goto et al 2012).…”
Section: Maternal-and Paternal-effect Screensmentioning
confidence: 99%